Suritech (sea urchin technology): accelerating and increasing the production process of sea urchin gonad in Spermonde Archipelago, Indonesia - La Nane; Syamsu Alam Ali (Fisheries and Society Publisher, 2021)
Suritech (sea urchin technology) is a technology machine for threshing sea urchin spines for the production of sea urchin egg kukure. Sea urchins are echinoderms whose entire body surface is covered with venomous spines. The purpose of this study was to determine the speed, capacity and production of sea urchin eggs based on the Suritech machine. The purpose of this research is to provide information on how to manufacture suritech machines in managing sea urchins. The Suritech machine is capable of producing 100 sea urchins per 4 minutes or 36.000 urchin per day. The production of sea urchin eggs by the Suritech machine is able to beat the production of sea urchin eggs in Japan, which is only around 27.000 tons per day. Thus, the use of the Suritech machine as a thresher of sea urchin spines is expected to increase fishermen's income and position South Sulawesi as the center of sea urchin egg production in Indonesia.